Digital Currency: The Future of Money - Matthew N. O. Sadiku; Uwakwe C. Chukwu; Janet O. Sadiku (Research Parks Publishers, 2023)
Digital currency is any currency that is available exclusively in electronic form. It has the potential to completely change how society thinks about money. It can reduce operating costs, increase efficiency, and enable a wide range of new applications. Digital currencies have become popular due to their convenient nature and for the fact that they allow users to transfer money quicker and in a simpler manner. However, many existing digital currencies have not yet seen widespread usage and banks generally do not accept or offer services for them. This paper provides an introduction to digital currencies.